The Impact of the Administrative System on the Effectiveness of Retribution Collection and Its Contribution to the Local Own-Source Revenue of Tapin Regency - Ramadhan, Muhammad; Ifransyah, Rosyid (Scholar Center, 2025)
Market service retribution, particularly from the market sector, is one of the strategic sources of Local Own-Source Revenue (PAD) in supporting regional development financing. However, in Tapin Regency, the management of market retribution receivables still faces various challenges, particularly related to a suboptimal administrative system. This study aims to analyze the influence of the administrative system on the effectiveness of market retribution collection and its contribution to increasing PAD in Tapin Regency. The research uses a qualitative descriptive approach, with data collected through in depth interviews with stakeholders at the Department of Trade and the Market Technical Implementation Unit (UPT Pasar). The findings indicate that limitations in the number of collectors, suboptimal distribution of retribution bills (SKRD), and the continued use of manual systems in billing and record keeping are major obstacles in retribution management. Additionally, disorganized archiving and the lack of an integrated digital system reduce the effectiveness of monitoring and accountability. Despite ongoing reform efforts through human resource development and digital application initiatives, implementation still requires careful planning and strong policy support. The study concludes that a well structured administrative system significantly influences the effectiveness of retribution collection and the realization of PAD from the market sector. Recommendations include accelerating the digitalization of the retribution system, increasing the number of collection personnel, and formulating comprehensive technical regulations for retribution implementation.